INVITRO ANTIOXIDANT ACTIVITIES OF VARIOUS LEAVES EXTRACTS FROM FIVE VARIETIES OF RAMBUTAN (Nephelium lappaceum) AND ITS CORRELATION WITH TOTAL FLAVONOID, PHENOLIC, CAROTENOID CONTENT - Fidrianny, Irda; Sukowati, Asih; Sukrasno, Sukrasno (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objectives: The objectives of this research were to study antioxidant activity from different polarities extracts of rambutan (Nephelium lappaceum) leaves using two methods of antioxidant testing which were 2-2-diphenyl-1-picrylhydrazyl (DPPH) and 2-2'-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) and correlation of total flavonoid, phenolic and carotenoid content in various extracts of rambutan leaves with DPPH and ABTS antioxidant activities. Methods: Extraction was performed by reflux using different polarity solvents. The extracts were evaporated using rotavapor. Antioxidant activities using DPPH and ABTS assays, determination of total phenolic, flavonoid and carotenoid content were conducted by spectrophotometry ultra violetvisible and its correlation with DPPH and ABTS antioxidant capacities were analyzed by Pearson's method. Results: RPH3 (ethanolic leaves extract of rapiah rambutan) had the highest DPPH scavenging capacity with inhibitory concentration 50 (IC50) 14.666 Î¼g/mL and the highest ABTS scavenging activity with IC50 12.826 Î¼g/mL. RPH3 had the highest phenolic content (29.46 g gallic acid equivalents/100 g), NON2 (ethyl acetate leaves extract of non-consumption rambutan) contained the highest total flavonoid (9.59 g quercetin equivalents/100 g), and NON1 (n-hexane leaves extract of non-consumption rambutan) had the highest carotenoid 10.99 g beta-carotene equivalent/100 g. Conclusions: There were positively and high correlation between total phenolic content in all of the leaves extracts with their antioxidant activity using DPPH and ABTS assays. DPPH scavenging activities in all of the samples gave linear result with ABTS scavenging capacities. Keywords: Antioxidants, 2-2-diphenyl-1-picrylhydrazyl, 2-2'-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid), Rambutan leaves, Flavonoid, Phenolic, Carotenoid.